2020
DOI: 10.1016/j.resp.2020.103443
|View full text |Cite
|
Sign up to set email alerts
|

Does the pathogenesis of SARS-CoV-2 virus decrease at high-altitude?

Abstract: Does the pathogenesis of SAR-CoV-2 virus decrease at high-altitude?, Respiratory Physiology and amp; Neurobiology (2020), doi: https://doi. J o u r n a l P r e -p r o o fHighlights  COVID-19 infection is decreased in populations living at an altitude of above 3,000 masl  Highland inhabitants may be less susceptible to SARS-CoV-2 virus infection due to physiological acclimatization to hypoxia  High-altitude environmental factors may contribute to reduce the virulence of SARS-CoV-2 ABSTRACTIn the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
235
5
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(270 citation statements)
references
References 18 publications
9
235
5
21
Order By: Relevance
“…In contrast to what other studies report regarding the greater spread of the in uenza virus in environments with lower air relative humidity [11], our data show that COVID-19 RI is higher in cities where RH is highest. These results are in line with those obtained by C Arias-Reyes, N Zubieta-DeUrioste, L Poma-Machicao, F Aliaga-Raudan, F Carvajal-Rodriguez, M Dutschmann, E Schneider-Gasser, G Zubieta-Calleja and J Soliz [3], which lists air dryness as one of the factors that control the spread of the virus at high altitudes. In working with climatic data from 5 large Brazilian cities (Manaus, Fortaleza, Brasília, Rio de Janeiro, and São Paulo), [12] showed that moderate relative air humidity (averages between 77.7 and 81.6%) favor the spread of this disease.…”
Section: Page 10/13supporting
confidence: 90%
See 3 more Smart Citations
“…In contrast to what other studies report regarding the greater spread of the in uenza virus in environments with lower air relative humidity [11], our data show that COVID-19 RI is higher in cities where RH is highest. These results are in line with those obtained by C Arias-Reyes, N Zubieta-DeUrioste, L Poma-Machicao, F Aliaga-Raudan, F Carvajal-Rodriguez, M Dutschmann, E Schneider-Gasser, G Zubieta-Calleja and J Soliz [3], which lists air dryness as one of the factors that control the spread of the virus at high altitudes. In working with climatic data from 5 large Brazilian cities (Manaus, Fortaleza, Brasília, Rio de Janeiro, and São Paulo), [12] showed that moderate relative air humidity (averages between 77.7 and 81.6%) favor the spread of this disease.…”
Section: Page 10/13supporting
confidence: 90%
“…The lower air density and greater distance between molecules in Brazilian cities located at higher altitudes could also reduce the inoculation of airborne viruses compared to sea level. C Arias-Reyes, N Zubieta-DeUrioste, L Poma-Machicao, F Aliaga-Raudan, F Carvajal-Rodriguez, M Dutschmann, E Schneider-Gasser, G Zubieta-Calleja and J Soliz [3] suggested that inhabitants of cities with altitudes above 3,000 m a.s.l. are less susceptible to developing effects caused by COVID-19 due to ultraviolet radiation and thinner air.…”
Section: Page 10/13mentioning
confidence: 99%
See 2 more Smart Citations
“…Although more studies are necessary, the rate of infection and the severity of the diseases seems different for people living in cities at high altitudes, where not only hipoxia is a major factor, but other factors such as air quality, solar radiation, and population density, could play a role in SARS-CoV-2 person-to-person transmission. Arias-Reyes et al (2020) suggested that there exists less rate of infection at high altitude possibly due to a lower level of expression of ACE2 compared to sea level. This observation is important, particularly since SARS-CoV-2 uses ACE2 as a point of infection for the cells (Ren et al, 2020).…”
Section: Introductionmentioning
confidence: 99%